The home edit : stay organized : the ultimate guide to making systems stick - Shearer, Clea, 1982-; Teplin, Joanna, 1979- (Clarkson Potter/Publishers, 2023)
"From the authors of The New York Times bestseller The Home Edit and The Home Edit Life and hosts of the Netflix series Get Organized with The Home Edit, comes a guide to the most important phase of getting organized: staying that way. It's one thing to get organized, but how do you make those systems stick? The Home Edit Stay Organized takes the intimidation and hesitation out of the maintenance involved to prevent you from abandoning your once-tidied systems or maybe help you to get organized in the first place! When you have a system that works, maintenance is a breeze. Think of a silverware drawer: It's obvious where each utensil goes, and so everyone in your house should know how to move the forks from the dishwasher to their spot. Often, when you're struggling to keep your home tidy, it's because your system is too complex and needs some tweaking--and this book will dig deeper to show you how. Throughout the book, Clea and Joanna reveal the important habits, debunk the myths, address the setbacks of being organized, and new and exclusive images show you how to tackle the hardest and trickiest spaces in each room in order to create a home that's organized for the long term. With inventory checklists, tips for getting the whole family on board to help, fans' frequently asked questions, and more, The Home Edit Stay Organized will help you move forward feeling calm, collected, and confidently organized--with humor, relatability, and beautiful imagery to enjoy along the way"--